Analisis Etos Kerja Guru Dalam Upaya Meningkatkan Karakter Disiplin Peserta Didik di Smpn 2 Klangenan - Septi Gumiandari; Tri Intan Febriany (Pusat Riset dan Inovasi Nasional, 2023)
Like electricity that has been cut off, the world of education in Indonesia hasbeen out since the emergence of the Covid-19 pandemic. Face-to-face conventionallearning is being replaced by technology. Teachers who are used to learning activitiesthat get students used to attending class now have to adapt to an all-digital life. Thepurpose of this research was to find out how to elaborate on the work ethic of teachersduring the new normal period at Junior High School Klangenan 2. In addition, this studyalso aims to explore what the teachers efforts are in improving the disciplinary characterof students at Junior High School Klangenan 2. This research used a qualitative researchmethod using a qualitative descriptive research design. The data that has been collectedis then analyzed by reducing, displaying, and providing conclusions. The results of thisstudy are that the work ethic of teachers at Junior High School Klangenan 2 can beassessed through interpersonal skills, initiative, and reliability. Meanwhile, the effortsmade by the teacher to improve the disciplinary character of students can be applied bygiving praise, gifts, reprimands, and sanctions